Some Novel Exponential and Complex Structural Properties of the Fisher Equation Arising in Mathematical Bioscience - Bulut, Hasan; Atas, Sibel Sehriban; Baskonus, Had Mehmet (E D P Sciences, 2017)
In this manuscript, we consider the Bernoulli sub-equation function method for obtaining new exponential and complex prototype structures to the Fisher Equation arising in Mathematical biosciences. We obtain new results by using the technique for new properties of model and for more understanding of properties of model. We plot two-and three-dimensional surfaces of the results by using Wolfram Mathematica 9. At the end of this manuscript, we submit a conclusion in the comprehensive manner.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Invasion; Gliomas